Evaluating the spatio-temporal development of coastal aquaculture: An example from the coastal plains of West Bengal, India. (15th November 2021) - Mandal, Bhanu Kumar; Islam, Aznarul; Sarkar, Biplab; Rahman, Abdur
Abstract: The present study examines the rapid expansion of commercial coastal aquaculture and transformation of agricultural land to coastal aquaculture during 1990–2020 in six coastal community development (C.D.) blocks of Purba Medinipur district of West Bengal. The coastal aquacultural land has increased by 109.93 km 2 while out of 64.41 km 2 agricultural land change, 35.91 km 2 has been transformed into coastal aquaculture during the same period. Moreover, the expansion of coastal aquaculture in 2030 predicted by the Markov chain model using satellite and ground data is estimated as 186.92 km 2 . The transition probability matrix of 2030 also reveals that ∼11.87% area of agricultural land of 2020 has a probability to be transformed to coastal aquacultural land in 2030. Therefore, the rapid agricultural land transformation to coastal aquaculture has also been discussed from the perspectives of geo-environmental hazards such as tropical cyclones and floods, coastal erosion as detected by digital shoreline analysis system (DSAS) model, salinity hazards measured by normalized difference salinity index (NDSI) and potential salinity (PS) index, and socio-economic drivers such as higher income return from the coastal aquaculture, and incentives from the government. Finally, the study based on the questionnaire survey addresses the issues such as changes in income portfolio and substitution of agricultural income by the income from coastal aquaculture. Moreover, the issue of food security has also been addressed and few future challenges have been identified. Graphical abstract: Image 1 Highlights: Agricultural land is increasingly transformed into coastal aquaculture areas. Coastal aquaculture area is predicted to expand by 26% during 2020–2030. Coastal erosion, tropical cyclone, flood, and soil salinity induce this transformation. Income differential between agriculture and aquaculture drives the transformation. Higher level of food security is found due to this transformation.